COMMON ERROR MADE BY ENGLISH STUDENTS’ IN WRITING INTRODUCTION SECTION - Ninda Nopriza (Teaching English and Language Learning English Journal, 2022)
The objective of the research was to find out common error made by English student in writing introduction section. The design of this research was descriptive qualitative method. The instrument of the research was table analysis of the students’ error in writing introduction section in thesis based on Caulfield (2020). The results of this research was the error made by students in writing introduction section found in 20 thesis were: first step 2 (not explain the previous study), second step 3 (not discuss the previous studies), third step 4 (not state the research problem), and the last one step 5 (did not describe the structure of the study). There were three common error in writing introduction of this research because have the similar total of the error, they are: 3 (not discuss the previous studies), third step 4 (not state the research problem), and the last one step 5 (did not describe the structure of the study). From the result, the researcher will give suggestion for the students who write the thesis in the future, the researcher suggest to add their knowledge about how to write good introduction section and use all of the steps of writing introduction section. it is important because introduction section is first section to be read by readers after reading the abstract and if readers are not impressed in reading this section, they will unlikely continue reading the research. Key Words: Thesis, Introduction section, Error